Gender panic, gender policy - Demos, Vasilikie P.; Segal, Marcia Texler, 1940- (Advances in gender research ;, 2017)
Using diverse theories and methods including analysis of online data, feminist critical discourse, fieldwork, grounded theory, and queer theory, this edited volume explores gender panic and policy in the United States as well as Argentina, Australia, Belarus, Japan, Russia, Sweden, and subnational populations. Contributors consider a range of issues from the meaning of learning to play the traditional female role in order to develop a contemporary heteronormative romantic relationship to the difficulties of fairly accommodating non-binary people in traditionally gendered settings or the problem of implementing a gender-neutral rape law in a prison system that is structurally gendered. Gendered policies pertaining, particularly, to women and their fertility as a result of panics over low birthrates are explored as are issues relating to the validation of and problems with binary gender categories in elite sports. The impact of UN gender equality initiatives including LGBT equality on nation-states is also examined.